Estudo do mecanismo de ação anti-inflamatório e imunoregulador do extrato hidroetanólico de Mandevilla longiflora (Desf.) Pichon (velame-branco) - Almeida, Danielle Ayr Tavares de (2016)
Mandevilla longiflora (Desf.) Müll. Arg (heterotypic synonym for Mandevilla longiflora Desf. Pichon, Mandevilla guarantica A. St.-Hil. Müll. Arg. and Echites Longiflorus Desf.) is an Apocynaceae family plant popularly known as ―velame‘, ―velame-branco‖, ―velamegrande‖, ―flor-de-babado‖, ―flor-de-babeiro‖, ―babado-de-Nossa-Senhora‖ ou ―jalapa-branca‖ and widely used in traditional medicine in the forms of of maceration, decoction and infusion as anti-inflammatory, anti-rheumatic, depurative, anti-syphilis and anti-ulcer effect. It is a subshrub native of South America, and in Brazil found in phytogeographical areas of Cerrado, Pampa and Foresta Atlântica. Despite its widespread use for treatment of inflammation, mainly by the population that living in the Centro-Oeste of Brazil, there are few studies that validate this pharmacological activity. This study aimed to elucidate the possible mode of action of hydroethanolic extract of M. longiflora (EHMl) on in vivo and in vitro tests, seeking to strengthen the scientific point of view, its popular use. Chronic inflammation models in rodents and culture cells of RAW 264.7 have been used. In a murine model of allergic asthma induced by ovalbumin was possible to assess the effect of EHMl on leukocyte influx into the airways, in the bronchoalveolar lavage fluid (BALF) and in the histopathological analysis of the lungs, beyond their effect on cytokine production (IL -4, IL-5 and IL-13), immunoglobulin (IgE) and leukotriene (LTB4). Through the stimulated murine macrophages were evaluated the participation of eicosanoids pathway (PGE2 and COX-2), the nitric oxide (Griess), cytokines (TNF, IL-1β, IL-10), chemotactic factors (ICAM- 1), and the expression of phosphorylated MAPK (p38, ERK-1/2 and JNK). The results obtained in the model of allergic asthma have shown that EHMl was able to reduce airway inflammation by decreasing the influx of leukocytes in the BAL and lung, inhibiting the production of cytokines and imunoglobulin and leukotriene. Furthermore, in vitro results demonstrated that the antiinflammatory effect of EHMl depends on the substances involved with the pathway of eicosanoids, with chemotactic molecules, cytokines and nitric oxide, but does not depend on the phosphorylation of MAPK. All these reultados reinforce, from a scientific point of view, the popular statement of M. longiflora as a potential anti-inflammatory therapy.